The relationship between team ability and home advantage in the English football league system - Ramchandani, G.; Millar, R.; Wilson, D. (German Journal of Exercise and Sport Research, 2021)
The existence of home advantage (HA) has been found in a variety of team sports including football. There is a paucity of research on the relationship between team ability and HA in domestic football leagues and the findings of previous studies are inconclusive. Using longitudinal data from the top four football divisions in England, this study investigates the influence of team ability on the HA of teams. The data collected for this study spans 24 seasons from 1995/96 to 2018/19 and includes 48,864 matches from the English Premier League (n= 9120), the Championship (n= 13,248), League One (n= 13,248) and League Two (n= 13,248). Team ability was interpreted in two ways: (1) the division in which teams play and (2) their league table position within each division. For both the divisional and positional analysis, HA was calculated as the ratio of home points to total points achieved by teams in each season under review. Evidence of a statistically significant HA was found in all four divisions and for teams of all abilities within each division. Small but statistically significant differences in HA were observed between divisions and between high, moderate and low ability teams within divisions.